Pembelajaran Berbasis Masalah Untuk Meningkatkan Hasil Belajar IPS Pada Siswa SDI Onekore 4 - Welu, Felix; Raji, Manggu Ngguna (JURNAL INOVASI EDUKASI, 2020)
The purpose of this research is to know the application of Problems Based Learning Strategy that can improve learning outcomes of Social studies on Class. IV Students at SDI. Onekore 4. This type of research is a classroom action research. The research subjects are Class IV student at SDI Onekore 4 that amount of 19 people. As for this research data is obtained by using test, Observation and documentation. The results of this study indicate an increase of learning outcomes on social subject after applied problem based learning strategies. This matter can seeing at increasing of presentation classical learning outcomes. in condition pracycles 21.05%, cycles I up to be 42.10% and on cycle II goes up to be 100%. The results of this study can be used as an alternative in the selection of learning strategies.